Peran Inkubasi Bisnis untuk Anggota KOPMA UNNES : Mendorong Lahirnya Jiwa Wirausahawan Muda - Atik Niswatul Khoir; Alldila Marizka Putri Lesmono; Novia Khoirunnikmah; Mifta Nurrohmah Awaliyah; Nina Farliana (STIKes Ibnu Sina Ajibarang, 2025)
Business incubation plays a strategic role in fostering entrepreneurial spirit among university students, particularly members of the Student Cooperative (KOPMA) at Universitas Negeri Semarang (UNNES). This study aims to examine how business incubation programs can encourage the emergence of young entrepreneurs by enhancing skills, providing mentorship, and supporting business idea development. Using a descriptive approach, the research analyzes aspects of business management, marketing strategies, and business development within the framework of a business incubator implemented in the KOPMA UNNES environment. Data were collected through interviews, questionnaires, observations, and relevant secondary sources. The findings show that well-structured incubation programs, supported by a conducive academic environment, can significantly improve the interest and capabilities of KOPMA members in initiating and managing their own businesses. This research provides valuable insights for designing effective entrepreneurship education policies and business development practices in higher education institutions.